2017
DOI: 10.3389/fpls.2017.00864
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salt Tolerance-related microRNAs and Their Targets in Maize (Zea mays L.) Using High-throughput Sequencing and Degradome Analysis

Abstract: To identify the known and novel microRNAs (miRNAs) and their targets that are involved in the response and adaptation of maize (Zea mays) to salt stress, miRNAs and their targets were identified by a combined analysis of the deep sequencing of small RNAs (sRNA) and degradome libraries. The identities were confirmed by a quantitative expression analysis with over 100 million raw reads of sRNA and degradome sequences. A total of 1040 previously known miRNAs were identified from four maize libraries, with 762 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 60 publications
4
42
0
7
Order By: Relevance
“…with salt tolerance, abiotic stresses in rice, and other crops. Manu Kumar et al elaborated on the relationship of OsSta2 with salt tolerance and abiotic stress in rice [52][53][54][55][56][57][58]. Salt tolerant varieties can be produced using marker-assisted selection or genetic engineering by introducing salt-tolerance genes [43].…”
Section: Discussionmentioning
confidence: 99%
“…with salt tolerance, abiotic stresses in rice, and other crops. Manu Kumar et al elaborated on the relationship of OsSta2 with salt tolerance and abiotic stress in rice [52][53][54][55][56][57][58]. Salt tolerant varieties can be produced using marker-assisted selection or genetic engineering by introducing salt-tolerance genes [43].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in plant miRNA research have been possible due to advancements in high-throughput sequencing. Plant miRNAs play crucial roles in biotic and abiotic stress responses, including in drought [38] and salt stress [39]. In the present study, 385 known miRNAs from 59 miRNA families and 94 novel miRNAs were identified from GLY and CK samples, and most of them were 21 nt in length, followed by 22 nt and 24 nt.…”
Section: Discussionmentioning
confidence: 61%
“…Since the first discovery of miRNAs, the basic understanding of how gene expression is controlled deeply changed. In the last ten years, studies demonstrated that miRNAs play crucial roles in modulating stress response, including salinity [78], drought [79], waterlogging [80], UV-B radiation and cold stress [81,82], and in several cases their biological role has been clarified. For instance, miR394 and miR397 have been reported to positively regulate cold tolerance via the CBF-dependent pathway [83,84], whereas miR319 activates the CBF regulon and triggers reactive oxygen species (ROS) elimination from the cells [85].…”
Section: Genomics and Machine Learning: A Case Study To Predict Diffementioning
confidence: 99%